ANALISIS PENDAPATAN USAHA TANI PADI SAWAH DI DESA PASAR TERUSAN KECAMATAN MUARA BULIAN KABUPATEN BATANG HARI - Astuti, Dia Fitri; Wahyuni, Ira; Ningsih, Rozaina (Agros Journal of Agriculture Science, 2024)
This study aims to determine 1) a general description of paddy rice farming, 2) analyze the income of paddy rice farming, 3) analyze the factors that affect the income of paddy rice farming in Pasar Terusan Village, Muara Bulian District, Batang Hari Regency. This research was conducted in Pasar Terusan Village, Muara Bulian District, Batang Hari Regency. This data comes from primary data and secondary data. This research uses a simple random sampling method. The Quantitative analysis method for the third objective uses a multiple linear regression econometric model of factors affecting the income of paddy rice farming. The results of the study 1) rice paddy farming in the research location is only done once the growing season is April-September. 2) The average income of paddy rice farming amounted to Rp 9,703,550 / ha / MT. 3) Factors that affect the income of paddy rice farming are land area, education level, farming experience, labor and the number of family dependents have a positive effect on the income of paddy rice farming and age factors have a negative effect on the income of paddy rice farming.